Contemporary Ancestors of de Bry, Hobbes, and Milton. - Nyquist, Mary (University of Toronto Quarterly)
By means of rhetorically patterned negation that is central to early modern proto-evolutionary, Euro-colonial discourses, indigenous American societies appear historically remote as well as culturally deficient. Yet if Americans are the contemporary ancestors of early modern Europeans, what place, if any, do they have within Christian redemptive history? This question does not concern Hobbes, whose state of nature is inextricably bound up with the historical anteriority of 'savage' societies. By contrast, de las Casas and Montaigne, who idealize civil privation, find praiseworthy continuities between American practices and those of ancient Israel or early Christianity. Both de Bry and Milton indirectly address allochronism by representing present-day Americans in connection with the Fall of a Europeanized Adam and Eve. Like de Bry's well-known engraving, "Paradise Lost" identifies fallen Eve and Adam with their American counterparts yet at the same time clearly distinguishes them. Milton's 'American,' however, remains unambiguously anterior to the epic's present. Lacking the complexly rendered subjective experience of Adam's shame and the awareness of loss the epic speaker shares with readers, "Paradise Lost's" 'American' does not benefit from the divinely initiated process of regeneration associated with clothing. By implication, indigenous Americans are dependent on outside intervention if they are to enter the Christian fold and, indeed, the forward movement of human history.